Algorytm komputerowo wspomaganego projektowania systemów treningowych - Kosendiak, Jan (The algorithm of the computer-aided designing of the training systems, 2005)
Designing of the Training System is one of the basic tasks of the Coach. And the skilled designing is the basic indicator of his level of education. The Designing is a sequence of subsequent activities, which forms the set of data named the Design of the Training Cycle. The Design includes set of assumptions, determinants, aims and means to achieve the aims. In this work the seven-step algorithm of training systems designing in is presented. At the same time, the conception of the system approach to the training process results in the optimization tasks, and solution of these makes possible to manage the sports training in efficient way. So, the seven step algorithm of training systems designing is, in fact, the sequence of optimization tasks. The Algorithm could be used as the base of software, when databases with information on rivalry demands in specific sport discipline, data on specific sportsmen, his aims, planed time structures of the training, planed loads and control results are used. Only then, the Algorithm presented in this work will be efficient tool and essentially aid for the Coach in his work.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 287-291